Trees for Food and Timber: are community interests in conflict with those of timber concessions in the Congo Basin? - Snook, Laura K.; Donn, P.; Duminil, J.; Fungo, R.; Kahindo, J.M.; Loo, J.; Maukonen, P.; Midoko Iponga, D.; Mikolo Yobo, C.; Monthe Kameni, F.; Muvatsi, P.; Ngongi, J.; et al. (Food and Agriculture Organization of the United Nations, 2015)
Much of the Congo Basin is managed for timber from dozens of species. More than 60% also produce non-timber products, including foods. For five multiple use tree species in Cameroon, Democratic Republic of Congo (DRC) and Gabon (Entandrophragma cylindricum, Baillonella toxisperma, Erythrophleum suaveloens, Dacryodes buettneri and Gambeya lacourtiana), we studied gathering and consumption by communities, edible caterpillars hosted, the densities of trees around villages and in concessions and the impacts of timber harvesting . We also studied the consumption of forest foods and the nutritional values of fruits and seeds of various tree species. Villagers walked up to six km during day trips to collect fruits or caterpillars, gathering from concessions if the village was within or near it. When foods were gathered from trees smaller than the cutting diameter (which varied by country and species), there was no conflict with timber harvesting. However, the volume of edible caterpillars hosted increased with diameter and harvestable trees were the most productive. Caterpillars, tree fruits and seeds provide fats, vitamins and minerals that complement agricultural foods. Densities of B. toxisperma, valued for its edible oil, were higher around villages than in concessions. The proportion of commercial trees harvested for timber varied from less than 3% to more than 50%, depending on the species. Different species had different geneflow distances, meaning viable regeneration could be expected with residual adults at different maximum distances. E. cylindricum had more effective dispersal than E. suaveolens. The production of timber and nontimber products can be sustained from the same concessions, for different stakeholders, with appropriate practices and arrangements.